Sponge spicules as proxy in Upper Quaternary lake deposits near Cianorte (PR): a tentative correlation with lakes of Central-Southern Brazil (NW Paraná and SE Mato Grosso do Sul - Rezende, Andréa Barbieri; Stevaux, José Cândido; Parolin, Mauro; Guerreiro, Renato Lada (Quaternary and Environmental Geosciences, 2018)
Researchers recognize the use of bio-proxy in Quaternary paleo environment reconstruction for more than 50 years. Among the bio-indicators, pollens and spores are, by far, the most used palynomorphs, followed by diatoms. However, oxidizing conditions can destroy and leach organic material. In such cases, sponge spicules, with siliceous skeleton, resist geochemist weathering and diagenesis, preserving in the sediment. This paper proposes an experimental correlation between sponge analyses obtained from lakes sediment in the NW Paraná and SE Mato Grosso do Sul States, Brazil, in a pioneering attempt of paleoclimatic data integration for the south-central Brazil. The structures used to identify the sponges were megascleres, microscleres and gemmoscleres. Both short- and long-distance correlations were satisfactory. Although a temporal and genetic correlation between lakes of NW Paraná and SE Mato Grosso do Sul lakes has been observed, their hydrological functioning was different.